Multiple choice testing and the retrieval hypothesis of the testing effect - Sensenig, Amanda E., author; DeLosh, Edward, advisor; Davalos, Deana, committee member; McCabe, David, committee member; De Miranda, Michael, committee member (Colorado State University. Libraries, 2010)
Taking a test often leads to enhanced later memory for the tested information, a phenomenon known as the “testing effect”. This memory advantage has been reliably demonstrated with recall tests but not multiple choice tests. One potential explanation for this finding is that multiple choice tests do not rely on retrieval processes to the same extent as other types of tests. The set of experiments reported here examines the retrieval hypothesis of the testing effect in multiple choice testing. Experiment 1 is a replication and extension of previous research (Roediger & Marsh, 2005) with the addition of a re-study comparison condition. Experiments 2a and 2b encouraged participants to engage in retrieval processes during multiple choice tests. Experiment 3 implemented a version of the remember/know paradigm in order to assess retrieval of individual items on a multiple choice test. Overall, multiple choice testing did not produce a memory advantage over re-studying the material in the experiments reported here. The results of these experiments are discussed in light of the retrieval hypothesis of the testing effect.
Covers not scanned.
Keywords: Multiple-choice examinations; Memory